An atomistic investigation of the composition dependence in SiGe alloys during Solid Phase Epitaxial Regrowth. (March 2016) - Payet, Anthony; Sklénard, Benoît; Barbé, Jean-Charles; Batude, Perrine; Tavernier, Clément; Gergaud, Patrice; Martin-Bragado, Ignacio
Abstract: The germanium fraction dependence of the Solid Phase Epitaxial Regrowth (SPER) rate in SiGe alloys has been investigated using a lattice kinetic Monte Carlo (LKMC) approach. Experiments show that the SPER rate is monotonically increasing with the addition of germanium. However, the extracted activation energy exhibits a non-linear evolution with the increase of germanium content. To investigate the influence of germanium in SiGe alloys, a comprehensive atomistic model is presented. The model focuses on the chemical bond types between the amorphous and the crystalline phases. As several recrystallization configurations exist at the amorphous–crystalline interface, a competition between them arises during SPER. This competition, implemented into a LKMC simulator, is able to reproduce several phenomena observed during SPER experiments on SiGe alloys: the monotonically increasing SPER rate and the non linear activation energy behavior regarding the germanium content as well as the temperature dependence on the extracted activation energy. The presented model is in close agreement with experimental data from literature. Graphical abstract: